Morphometric analysis of Bhopal lake catchment using geospatial technology - THAKUR, ARADHANA; NEMA, A. K.; JAISWAL, R. K.; MISHRA, C. D. (Journal of Soil and Water Conservation, 2020)
Morphometric analysis of any basin with the help of geospatial technology gives appropriate results to understand the configuration of earth surface, shape and dimension of its landform. At present Remote Sensing (RS) and Geographical Information System (GIS) techniques are being effectively used as tools to characterize the basin geometry and hydrological response behavior of the watershed. This study aims to analyze the basin morphometric parameters including linear, aerial and relief aspects of the Bhopal lake catchment using viable tool RS and GIS,which are the basic requirement for site selection, planning for soil and water conservation measures and their designing. The present study covered an area of 364.93 km2 out of which 20.074 km2 is submerged. The detailed map prepared from toposheets and satellite imagery and basin have been divided into 24 sub-watershed where area of sub-watersheds varies from 3.78 (WS-4) to 40.33 (WS-11) km2 with highest 4th order stream having dendritic drainage pattern.